Children’s books about scientists convey demotivating messages - Jessica R. Gladstone; Gabrielle Applebaum; Andrei Cimpian (Proceedings of the National Academy of Sciences, 2026)
Biographies of scientists are widely used to spark children’s interest and broaden participation in science. In telling the stories of successful scientists, these books convey implicit “recipes for success”—yet no study has systematically examined whether these recipes align with what motivation research recommends. Here, we provide the first large-scale analysis of motivational messages in children’s science biographies (422 best-selling books, 1,355 protagonists). Four main findings emerged. First, scientific ability was portrayed equally often as fixed and as malleable, a pattern unlikely to support motivation. Second, interest in science was overwhelmingly portrayed as fixed: Most scientists were said to be captivated by science from a young age. Third, scientists in physics, engineering, and computer science were portrayed as more reliant on fixed ability than scientists in other fields. Fourth, biographies of female scientists disproportionately emphasized effort even after adjusting for the obstacles they faced, consistent with stereotypes attributing women’s success to hard work over talent. These findings suggest that well-intentioned efforts to diversify science through role model exposure in children’s science biographies may fall short.